2020
DOI: 10.3389/fneur.2020.00505
|View full text |Cite|
|
Sign up to set email alerts
|

Quantitative Evaluation of a New Posturo-Locomotor Phenotype in a Rodent Model of Acute Unilateral Vestibulopathy

Abstract: Vestibular pathologies are difficult to diagnose. Existing devices make it possible to quantify and follow the evolution of posturo-locomotor symptoms following vestibular loss in static conditions. However, today, there are no diagnostic tools allowing the quantitative and spontaneous analysis of these symptoms in dynamic situations. With this in mind, we used an open-field video tracking test aiming at identifying specific posturo-locomotor markers in a rodent model of vestibular pathology. Using Ethovision … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
48
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(60 citation statements)
references
References 78 publications
8
48
0
4
Order By: Relevance
“…To assess the functional consequences of unilateral optogenetic stimulation of VN on locomotor functions, we next studied several parameters previously identified as biomarkers of locomotor dysfunctions in rodents (Rastoldo et al 2020). These parameters were monitored on animals placed in an open field before, 5 minutes after, and 1 hour after optogenetic stimulation.…”
Section: Vn-vglut2+ Activation Provokes Short Term Disturbances Of Lomentioning
confidence: 99%
“…To assess the functional consequences of unilateral optogenetic stimulation of VN on locomotor functions, we next studied several parameters previously identified as biomarkers of locomotor dysfunctions in rodents (Rastoldo et al 2020). These parameters were monitored on animals placed in an open field before, 5 minutes after, and 1 hour after optogenetic stimulation.…”
Section: Vn-vglut2+ Activation Provokes Short Term Disturbances Of Lomentioning
confidence: 99%
“…Since vestibular receptors detect accelerations, this parameter is particularly relevant to assess vestibular dysfunction following UVN (Rastoldo et al, 2020). We observed a significant increase of this parameter after UVN for both UVN+placebo and UVN+met groups in the compensated phase ( Figure 8D).…”
Section: Mean Acceleration During Free Locomotionmentioning
confidence: 83%
“…We assessed the posturo-locomotor activity of the animals under ecological conditions by measuring different parameters known to be affected by UVN in rats (see (Rastoldo et al, 2020) for details). At the beginning of the session, rats were placed individually in the center of an open field (80x80x40cm) for 10 minutes and tracked with Ethovision TM XT 14 software (Noldus).…”
Section: Quantitative Assessment Of the Posturo-locomotor Activitymentioning
confidence: 99%
“…Ours is the first study to distinguish patients with vestibular pathology from healthy controls and non-vestibular dizzy patient controls based on the ratio between walking and turning while completing the instrumented TUG. This is a critical result as it has been reported that typical measures of gait, such as the 10-meter walking test, may not provide consistent results in screening patients with vestibular impairments [10,[35][36][37][38].…”
Section: Discussionmentioning
confidence: 97%